Weed Control Efficacy and Crop-Weed Selectivity of a New Bioherbicide WeedLock - Mahmudul Hasan; Anis Syahirah Mokhtar; Adam Mustafa Rosli; Hafizuddin Hamdan; Mst. Motmainna; Muhammad Saiful Ahmad-Hamdani (Agronomy, 2021)
Plant-based bioherbicides could be an effective alternative to current chemical herbicides for sustainable agriculture. Therefore, this research evaluated the weed control efficacy and crop-weed selectivity of the new plant-derived bioherbicide WeedLock compared to commercial herbicides in glasshouse and field conditions. In the glasshouse, the herbicides applied were WeedLock (672.75, 1345.50, 2691.00 L ha−1), glyphosate isopropyl-amine, and glufosinate-ammonium (1, 2, 4 L ha−1), over the untreated (control) on six weeds and four crops. In the field trial, typical weeds were allowed to grow at a uniform density across plots (2.5 × 2.5 m), and WeedLock (1345.50, 2691.00 L ha−1), glyphosate isopropyl-amine, and glufosinate-ammonium (2, 4 L ha−1) were applied along with untreated plot (control). A randomized complete block design was set with four replications for glasshouse and field experiments. WeedLock at 1345.50 L ha−1 showed efficacy similar to glyphosate isopropyl-amine and glufosinate-ammonium at 2 L ha−1 for Ageratum conyzoides L. in the glasshouse. Applied herbicides killed all tested crops except Zea mays L. at 1345.50 L ha−1 (WeedLock). WeedLock showed more than 50% efficacy at 35 days after spray, while 65% was produced by glyphosate isopropyl-amine and glufosinate-ammonium compared to the untreated plot (control). WeedLock has excellent potential to control weeds in both glasshouse and field conditions and showed a non-selective character.